Pengaruh Struktur Kepemilikan dan Ukuran Perusahaan Terhadap Kinerja Intellectual Capital - Nicma, Hanifa Ainun; Tumirin (Fakultas Ekonomi dan Bisnis Unram, 2024)
The focus of the research is how a company's ownership structure and size impact intellectual capital. This research uses multiple linear regression and purposive sampling to examine 37 companies listed on the Indonesia Stock Exchange (BEI) in 2022. Intellectual capital is not affected by company size, institutional ownership, or foreign ownership; however, management ownership influences 5%. Those who wish to conduct further research can use this research as a reference regarding ownership structure and company size on intellectual capital performance.